Franciszkańscy misjonarze w Peru - Szyszka, Tomasz (Annales Missiologici Posnanienses, 2023)
The history of evangelization in Peru, which started at the very onset of the 16th century is connected with the presence of the missionaries of the Franciscan Order, who played a major role in the building of Church structures on the territory of the former Inca empire. However, their main contribution was an effective evangelization of the indigenous peoples through the use of innovative methods (music, singing and art, organizing schools for Indians, knowledge of indigenous languages, protection of Indians against excessive exploitation). In this activity they were urged by their Franciscan charisma summed up in the greeting “Peace and good”. Their missionary commitment was realized not only in the Andean world, but over time expanded across the Amazon Selva.